Psychology of women and gender - Liss, Miriam, ....-; Richmond, Kate, ....-; Erchull, Mindy J., ....- (New York : Norton & company, 2019)
Placing a central focus on the concerns of students today, this text deals with important, timely topics such as intersectionality, transgender issues, sexualisation and objectification. It combines up-to-date research with an approachable and engaging writing style, while also providing students with hands-on exercises and thought-provoking debate topics. Flexible teaching resources support every kind of instructor's course.